PADRÃO DE ESPECIALIZAÇÃO DO COMÉRCIO INTERNACIONAL DO MARANHÃO (1999-2016) - Laís Viera Trevisan; Alison Geovani Schwingel Franck; Rodrigo Abbade da Silva; Daniel Arruda Coronel (Revista de Políticas Públicas, 2019)
This study aimed to evaluate the specialization pattern in international trade in the state of Maranhão, identifying the most dynamic productive sectors in the period between 1999 and 2016. In this sense, the Revealed Symmetric Comparative Advantage (IRSCA) indicator was calculated, as well as the Intra-industry trade index (IIT), the Industry Concentration of Exports (ICS), and the Import Coverage Ratio (IC). The results of the calculations of the RSCA and the IIT indicate that the state has two competitive sectors in the international market: common metals and chemicals. In addition to these indicators, the ICS indicated that Maranhão has an export basket concentrated in a few sectors, with little diversification, and the IC pointed out that the footwear and leather, textiles and metals are the sectors that most exceed imports in relation to the exported value.